Profil Ekspresi mRNA Gen Murine Double Minute2, Kruppel-Like Factor4, dan c-Myc pada Fibrosarkoma - Humaryanto Humaryanto; M. Nurhalim Shahib; Yoni Fuadah Syukriani; Nucki Nursjamsi Hidayat (Universitas Islam Bandung, 2017)
Fibrosarkoma hanya terjadi 1–3% dari seluruh keganasan jaringan lunak. Hingga saat ini etiologi fibrosarkoma belum diketahui dengan pasti. Beberapa faktor dapat menjadi penyebab patogenesis fibrosarkoma antara lain radiasi, terpapar zat kimia tertentu, serta infeksi human herpes virus 8 (HHV8) dan Epstein-Barr virus (EBV). Penelitian terkini menunjukkan bahwa banyak sarkoma terkait dengan mutasi genetik. Penelitian ini bertujuan melihat profil ekspresi mRNA gen Krüppel-like Factor4, Murine Double Minute2, dan c-Myc pada fibrosarkoma menggunakan teknik real time PCR kuantitatif (quantitative real time PCR, qRT-PCR). Analisis data menggunakan metode kuantititatif relatif 2-ΔΔCt. Penelitian ini menggunakan 10 sampel kasus fibrosarkoma yang ditemukan di Kota Jambi dari tahun 2011–2015. Hasil ΔCt (+SD) MDM2, KLF-4, dan c-Myc disusun dari nilai yang terkecil hingga tertinggi adalah 1,85±2,14; 2,06±3,86; 2,9±2,66 secara berurutan. Dibanding dengan level ekspresi dengan GAPDH sebagai housekeeping gene, gen MDM2 dan KLF-4 relatif menurun dua kali lipat, sedangkan gen c-Myc relatif menurun lebih dari tiga kali lipat. Simpulan, penelitian ini menunjukkan bahwa pada kasus fibrosarkoma, gen c-Myc disupresi lebih kuat dibanding dengan gen MDM2 dan KLF-4.STUDIES ON MRNA GENE EXPRESSION OF MDM2, KLF4,AND C-MYC IN FIBROSARCOMAFibrosarcoma is a rare soft tissue sarcoma, reported only 1–3% of all soft tissue sarcomas. Like any other soft-tissue sarcomas the definitive caused has not yet understood. Recognized causes include exposure to ionizing radiation, various physical and chemical factors, infection with human herpes virus (HHV8) and Epstein-Barr virus (EBV). Current research indicates many sarcomas are associated with genetic mutations. In this study, we investigated profile of mRNA gene expression KLF4, MDM2, and c-Myc of RNA in fibrosarcoma cases. The genes expression was examined using quantitative real time PCR (qRT-PCR) and we analyzed the relative gene expression using the 2-ΔΔCt method. Ten samples of fibrosarcoma cases found in Jambi city from 2011 to 2015 were used. The three targeting genes were placed in the order from lowest to highest base on their ΔCt values compared to internal control genes using GAPDH genes. The results are as follows: MDM2 1.85±2.14, KLF-4 2.06±3.86, and c-Myc 2.9±2.66 respectively. A relative quantification by normalized target gene relative to GAPDH, describes the changes in expression of three genes. The status of MDM2 and KLF-4 were relatively decreased expression by 2 fold, and the states of c-Myc were relatively decreased by more than 3 fold. This suggest that in fibrosarcoma the c-Myc gene are suppressed stonger than those MDM2 and KLF-4 genes.